The opioid effects of gluten exorphins: asymptomatic celiac disease - Pruimboom, Leo (J Health Popul Nutr, 2015)
Gluten-containing cereals are a main food staple present in the daily human diet, including wheat, barley, and rye. Gluten intake is associated with the development of celiac disease (CD) and related disorders such as diabetes mellitus type I, depression, and schizophrenia. However, until now, there is no consent about the possible deleterious effects of gluten intake because of often failing symptoms even in persons with proven CD. Asymptomatic CD (ACD) is present in the majority of affected patients and is characterized by the absence of classical gluten-intolerance signs, such as diarrhea, bloating, and abdominal pain. Nevertheless, these individuals very often develop diseases that can be related with gluten intake. Gluten can be degraded into several morphine-like substances, named gluten exorphins. These compounds have proven opioid effects and could mask the deleterious effects of gluten protein on gastrointestinal lining and function. Here we describe a putative mechanism, explaining how gluten could “mask” its own toxicity by exorphins that are produced through gluten protein digestion.